Effects of 12-Month Valsartan Therapy on Glycation and Oxidative Stress Markers in Type 2 Diabetic Subjects With Hypertension - Hirose, Hiroshi; Itoh, Hiroshi; Komiya, Naoko; Saisho, Yoshifumi; Saito, Ikuo (International Heart Journal, 2008)
Although it has been reported that angiotensin II receptor blockers inhibited the formation and accumulation of advanced glycation endproducts (AGEs) in vitro and in vivo, whether they can do so clinically is not clear. We investigated the effects of 12-month valsartan therapy on various markers of inflammation, glycation, and oxidation in type 2 diabetic subjects with hypertension. We started 40 mg/day valsartan treatment in 15 type 2 diabetic patients with hypertension. In 6 patients, the dose of valsartan was increased to 80 mg/day after 6 months and maintained until 12 months. Metabolic parameters including BMI and serum high molecular weight (HMW)-adiponectin, high-sensitivity C-reactive protein (hs-CRP) as an inflammation marker, AGEs, paraoxonase activity, platelet-activating factor (PAF)- acetylhydrolase activity, and urine 8-isoprostane levels were measured at baseline and after 6 and 12 months of treatment. Urine microalbumin level and carotid artery intima-media thickness (IMT) were also measured. Even after valsartan therapy, the blood pressure levels of the patients were not decreased significantly. Serum AGEs and urine 8-isoprostane levels decreased at both 6 and 12 months (P < 0.05 for both), although other metabolic and oxidative markers were unchanged. Though urine microalbumin levels tended to be decreased after 6 and 12 months of valsartan treatment, the changes were not significant. Mean IMT at 12 months was not changed from the baseline value. In conclusion, the findings suggest that treatment with valsartan, even at a low dose, may ameliorate some glycation and oxidative stress markers independently of an effect on blood pressure in hypertensive type 2 diabetic subjects.